Pengaruh Pergantian Manajemen, Opini Audit, Ukuran KAP dan Ukuran Perusahaan Klien Terhadap Pergantian KAP - Deka Veronica; Asrini Asrini (LPPM - STIE SAKTI ALAM KERINCI, 2018)
This study aims to prove: (1) The influence of management changes, audit opinion, the size of the public accounting firms, and the size of the company to auditor changes (2) The influence of management changes to auditor changes (3) The audit opinion to auditor changes (4) The size of the public accounting firms to auditor changes, and (5) The size of company to auditor changes. The research population was property and real estate sector, infrastructure, utilities and transportation sectors, and trade, services and investment sectors the was registered in stock exchange in 2011-2016. Collecting data using purposive sampling method. Samples used in this study were 44 companies. Hypothesis testing is done with logistic regression analysis. Result of this research conclude that: (1) The influence of management changes, audit opinion, the size of the public accounting firms, and the size of the company together influential to auditor changes (2) The management changes have a influence on auditor changes (3) The audit opinion doesn’t have a influence on auditor changes (4) The size of the public accounting firm doesn’t have a influence on auditor changes (5) The size of company have a influence on auditor changes.